Dukungan Keluarga Dengan Kualitas Hidup Pada Pasien Kanker Payudara Yang Menjalani Kemoterapi - Hendra Dwi Cahyono; Ni Putu Ira; Hendro Prasetyo (Jurnal Keperawatan Malang, 2023)
Strong support from the family plays a protective role in overcoming the impact of life stress and improving the patient's life. The many impacts of chemotherapy treatment that is undertaken, will become a long-term problem that will affect the patient's quality of life. In unfavorable psychological conditions due to chemotherapy, cancer patients need the support of the closest people, the family is the patient's closest person who will provide comfort and peace. Prevalence of RS. Level III Baladhika Husada Jember in the Medical service section in January. There will be 2,142 cases of breast cancer in 2021. As for the number of breast cancer patients recorded in medical record data, patients undergoing chemotherapy in the Flamboyan Room have increased every month. In October 2021 there were 198 patients, in November 206 patients, in December 212 patients. This research method is correlation with cross-sectional approach. with 86 samples using a non-probability sampling technique with consecutive sampling and using a measuring instrument used on variables using a questionnaire. The results of the analysis using the Spearman Rank Tests ? 0.05 obtained a p-value ( 0.00 < ? ( 0.05) so that it can be concluded that there is a relationship between family support and quality of life in breast cancer patients undergoing chemotherapy at a level hospital. III Baladhika Husada Jember.Support given by the family can be in the form of attention or playing an active role in the treatment and therapy programs currently being undertaken by breast cancer patients.Involvement of family members in motivating them to maintain their condition and perform chemotherapy.